2023
DOI: 10.3390/ma16124393
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Magnetocaloric Performance of the Fe87Ce13−xBx (x = 5, 6, 7) Metallic Glasses and Their Composite

Abstract: The novel Fe87Ce13−xBx (x = 5, 6, 7) metallic glass (MG) ribbons were fabricated in this work. The compositional dependence of glass forming ability (GFA), magnetic and magnetocaloric properties of these ternary MGs, and the mechanism involved was investigated. The GFA and Curie temperature (Tc) of the MG ribbons were found to improve with the boron content, and the peak value of magnetic entropy change (−ΔSmpeak) reaches a maximum of 3.88 J/(kg × K) under 5 T when x = 6. Based on the three results, we designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Improving the −∆S m peak near RT as much as possible seems to be an effective way to improve the magnetocaloric properties of Fe-based MGs. In the previous study of Fe-Ce-B ternary MGs [56], Ce was partially replaced by B, and it was found that with the decrease in Ce atoms, the antiferromagnetic coupling between Ce and Fe atoms was weakened, resulting in the enhancement of 3d-3d interaction between Fe atoms and thus T c increased. In the study of Fe-Zr-B ternary MGs [32], it was found that by replacing Zr with Ce, T c decreased from 306 K to 283 K. In summary, the composition dependence of the MCE in the Fe-Zr-Pr-B quaternary amorphous alloys system can be explained by the antiferromagnetic coupling between Ce and Fe atoms and the Ce-Pr interaction caused by the introduction of Ce atoms, which may lead to the weakening of the 3d-3d interaction between Fe atoms.…”
Section: Resultsmentioning
confidence: 97%
“…Improving the −∆S m peak near RT as much as possible seems to be an effective way to improve the magnetocaloric properties of Fe-based MGs. In the previous study of Fe-Ce-B ternary MGs [56], Ce was partially replaced by B, and it was found that with the decrease in Ce atoms, the antiferromagnetic coupling between Ce and Fe atoms was weakened, resulting in the enhancement of 3d-3d interaction between Fe atoms and thus T c increased. In the study of Fe-Zr-B ternary MGs [32], it was found that by replacing Zr with Ce, T c decreased from 306 K to 283 K. In summary, the composition dependence of the MCE in the Fe-Zr-Pr-B quaternary amorphous alloys system can be explained by the antiferromagnetic coupling between Ce and Fe atoms and the Ce-Pr interaction caused by the introduction of Ce atoms, which may lead to the weakening of the 3d-3d interaction between Fe atoms.…”
Section: Resultsmentioning
confidence: 97%